Curriculum for Excellence: A cross-sector investigation of Scottish teachers mathematical beliefs of problem solving - Paul Argyle McDonald (University of Aberdeen, School of Education, 2016)
This paper explores Scottish primary and secondary teachers' mathematical beliefs of problem solving. Curriculum for Excellence advocates the centrality of problem solving within the nucleus of learning and teaching of mathematics. This transformational change has reconceptualised problem solving as the panacea to raising attainment at all levels of school mathematics. Teachers' beliefs are seen as pivotal to the successful enactment of any curricular reform. It has been widely assumed that cross-sector mathematical perspectives are compatible with problem solving. A mixed methods explanatory sequential design study was conducted in which online questionnaires and semi-structured interviews were used to collect data from in-service teachers. More specifically, it explored beliefs regarding the nature of mathematics, the learning of mathematics and the teaching of mathematics. Factor analysis identified three belief systems reliable with a social constructivist, problem solving and transmissionist orientation. It found that teachers' deep-rooted mathematical beliefs are not aligned to one particular group of belief systems but are embedded mutually within a cluster and that inconsistencies exist between beliefs and reported practice. Statistically significant differences exist between primary and secondary sectors. Factors impacting on teachers' mathematical beliefs are identified.